Duty-period-based network model for airline crew rescheduling - Rüdiger Nissen; Knut Haase (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2004)
Airline rescheduling is a relatively new field in airline Operations Research but increasing amounts of traffic will make disturbances to the original schedule more frequent and more severe, and thus the need to address the various problems arising from this situation with systematic, cost-efficient approaches is becoming more urgent. One such problem is crew rescheduling where after a disturbance in the crew schedule the aim is to determine new crew assignments that minimize the 'impact' on the original schedule. 'Impact' is most often defined as the number of changes in the crew schedule, but could also be seen as either the costs incurred by the changes or the period of time until full recovery is achieved. In this work we present a new duty-period-based formulation for the airline crew rescheduling problem that uses a new type of resource constraints to efficiently cover the various labor regulations and that is tailored to the needs of European airlines, as well as a solution method based on branch-and-price. The solution method is tested on various rescheduling scenarios, each with several distinct cases. Especially solution time is a critical factor and the results show that the solution method is capable of providing solutions within the short period of time available to a rescheduler after a disturbance occurs.
Keywords: 650; transportation; crew scheduling; rescheduling; irregular operations; disruption management; crew recovery; operational crew scheduling; column generation; Luftverkehr; Personaleinsatzplanung; Scheduling-Verfahren; Theorie